Situational Leadership Style, Organizational Culture and Organizational Commitment on Employee Performance - Munawir Nasir (Golden Ratio of Data in Summary, 2022)
This study aims to analyze the effect of situational leadership styles, organizational culture, and organizational commitment on employee performance and to determine the most dominant variable influencing the performance of the Regional Office employees of Tanete Riattang Barat District, Bone Regency. This research was conducted from October to December 2021. The population of this study was 62 employees of the Tante Riattang Barat District Office, Bone Regency. The analysis used is descriptive to explain the characteristics of respondents and descriptive research, while to analyze quantitative data, multiple regression analysis is used through the SPSS program. The results showed that situational leadership style, organizational culture, and organizational commitment jointly affect the performance of the employees of the Regional Office of the District of Tanete Riattang Barat, Bone Regency, and the variable that has the most dominant influence is organizational commitment.